2014
DOI: 10.1016/j.bbmt.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Treosulfan, Fludarabine, and 2-Gy Total Body Irradiation Followed by Allogeneic Hematopoietic Cell Transplantation in Patients with Myelodysplastic Syndrome and Acute Myeloid Leukemia

Abstract: Allogeneic hematopoietic cell transplantation (HCT) offers curative therapy for many patients with myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). However, post-HCT relapse remains a major problem, particularly in patients with high-risk cytogenetics. In this prospective phase II trial we assessed the efficacy and toxicity of treosulfan, fludarabine and 2 Gy total body irradiation (TBI) as conditioning for allogeneic HCT in patients with MDS or AML. Ninety-six patients with MDS (n=36; 15 RMCD; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…Approaches to decrease the incidence of disease relapse might consist of increasing the intensity of the conditioning regimen (for example with the addition of treosulfan (49) or with radiolabeled antibodies (50, 51)) or adding diseasetargeted therapies after transplantation (52,53). Furthermore, recent studies have demonstrated that triple postgrafting immunosuppression with cyclosporine, MMF and sirolimus improved outcomes in MUD patients conditioned with fludarabine þ 2 Gy TBI (54), while administration MMF at the dose of 3g/day (instead of 2 g/day) decreased the incidence of grade II-IV acute GVHD without affecting infection-related mortality of other transplantation outcomes in the double CBT setting (55).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to decrease the incidence of disease relapse might consist of increasing the intensity of the conditioning regimen (for example with the addition of treosulfan (49) or with radiolabeled antibodies (50, 51)) or adding diseasetargeted therapies after transplantation (52,53). Furthermore, recent studies have demonstrated that triple postgrafting immunosuppression with cyclosporine, MMF and sirolimus improved outcomes in MUD patients conditioned with fludarabine þ 2 Gy TBI (54), while administration MMF at the dose of 3g/day (instead of 2 g/day) decreased the incidence of grade II-IV acute GVHD without affecting infection-related mortality of other transplantation outcomes in the double CBT setting (55).…”
Section: Discussionmentioning
confidence: 99%
“…Treosulfan, a novel alkylating agent, has shown promise in single-arm clinical trials of younger patients. 36,37 Another myeloablative regimen with reduced toxicity uses a combination of fludarabine and high-dose BU (Flu/Bu4). [38][39][40] The Flu/Bu4 regimen has been compared with BU/CY in patients with leukemia or MDS, showing increased relapse and no benefit in terms of NRM for Flu/Bu4.…”
Section: Efficacy-is There An Ideal Conditioning Regimen?mentioning
confidence: 99%
“…Slower recovery of naive CD45RAþ T cells and T-cell receptor excision circle levels and more diverse T-cell repertoire have been also associated with the use of high-dose total body irradiation as part of conditioning regimen for UCBT recipients, especially in adults [52,55,56]. Novel ATG-free, reduced-intensity regimens [57,58], alternative to either high-dose myelo-ablatives or NMA, have been shown to be highly effective in adult patients with hematologic malignancies. Whether or not these new preparative regimens will have less impact on immune reconstitution still must be determined, although the preliminary results are encouraging and might contribute to further improving the outcomes of UCBT.…”
Section: Discussionmentioning
confidence: 99%